DNA recovery from used malaria RDT to detect Plasmodium species and to assess Plasmodium falciparum genetic diversity: a pilot study in Madagascar - Voahangy Hanitriniaina I. Andrianaranjaka; Elisabeth Ravaoarisoa; Tovonahary A. Rakotomanga; Fanomezantsoa Ralinoro; Danielle A. Doll Rakoto; Ranjàna H. Randrianarivo; Victor Jeannoda; Arsène Ratsimbasoa (Malaria Journal, 2022)
Abstract Background Rapid diagnostic tests (RDT) are widely used for malaria diagnosis in Madagascar, where Plasmodium falciparum is the predominant species. Molecular diagnosis is essential for malaria surveillance, but requires additional blood samples for DNA extraction. Used RDTs is an attractive alternative that can be used as a source of DNA. Plasmodium falciparum genetic diversity and multiplicity of infection, usually determined by the genotyping of polymorphic regions of merozoite surface proteins 1 and 2 genes (msp1, msp2), and the repeated region RII of the glutamate-rich protein gene (glurp) have been associated with malaria transmission levels and subsequently with the impact of the deployed control strategies. Thus, the study aims to use RDT as DNA source to detect Plasmodium species, to characterize Plasmodium falciparum genetic diversity and determine the multiplicity of infection. Methods A pilot study was conducted in two sites with different epidemiological patterns: Ankazomborona (low transmission area) and Matanga (high transmission area). On May 2018, used RDT (SD BIOLINE Malaria Ag P.f/Pan, 05FK63) were collected as DNA source. Plasmodium DNA was extracted by simple elution with nuclease free water. Nested-PCR were performed to confirm Plasmodium species and to analyse P. falciparum msp1, msp2 and glurp genes polymorphisms. Results Amongst the 170 obtained samples (N = 74 from Ankazomborona and N = 96 from Matanga), Plasmodium positivity rate was 23.5% (40/170) [95% CI 17.5–30.8%] by nested-PCR with 92.2% (37/40) positive to P. falciparum, 5% (2/40) to Plasmodium vivax and 2.5% (1/40) to P. falciparum/P. vivax mixed infection. Results showed high polymorphisms in P. falciparum msp1, msp2 and glurp genes. Multiple infection rate was 28.6% [95% CI 12.2–52.3%]. The mean of MOI was 1.79 ± 0.74. Conclusion This pilot study highlighted that malaria diagnosis and molecular analysis are possible by using used malaria RDT. A large-scale study needs to be conducted to assess more comprehensively malaria parasites transmission levels and provide new data for guiding the implementation of local strategies for malaria control and elimination. Trial registration Retrospectively registered